Typification of Linaria badalii (Plantaginaceae, Antirrhineae), and the problem of the original material used to describe the species - Ferrer Gallego, Pedro Pablo; Sáez, Llorenç (Mediterranean Botany, 2025)
The typification of the name Linaria badalii (Plantaginaceae, Antirrhineae), is discussed. The designation of the nomenclatural type is based on an assessment of Loscos’s original material collected by Antonio Badal in Las Parras de Martín (Teruel, Spain). The name is lectotypified using a specimen from Loscos’s herbarium preserved in The Royal Aragonese Economic Society of Friends of the Country (RAESFC) in Zaragoza (Spain). However, the lectotype lacks seeds, and the seeds have relevant diagnosis characters considered useful for taxonomy. Therefore, a specimen conserved in the Herbarium of the Royal Botanic Garden of Madrid (at MA) and also collected by Badal in the same locality that the original material used by Loscos to describe his species is designated as the epitype of L. badalii in order to avoid any ambiguity in the interpretation of the lectotype